Bacterial Pneumonia and Stroke Risk: A Nationwide Longitudinal Followup Study - Wang, Joyce En-Hua; Tsai, Shih-Jen; Wang, Yen-Po; Chen, Tzeng-Ji; Wang, Tso-Jen; Chen, Mu-Hong (Current Neurovascular Research, 2023)
Background: Pneumonia causes significant morbidity and mortality and has been associated with cardiovascular complications. Our study aimed to investigate the incidence of ischemic and hemorrhagic strokes following bacterial pneumonia. Methods: Between 1997 and 2012, 10,931 subjects with bacterial pneumonia and 109,310 controls were enrolled from the Taiwan National Health Insurance Research Database, and were followed up to the end of 2013. The risk of stroke was estimated in Cox regression analyses with hazard ratios (HRs) and 95% confidence intervals (CIs). Results: When compared to the control group, subjects in the bacterial pneumonia group had a higher incidence of developing ischemic stroke (2.7% versus 0.4%, p <0.001) and hemorrhagic stroke (0.7% versus 0.1%, p <0.001). The risk of stroke increases with repeated hospitalizations due to bacterial pneumonia. Across bacterial etiologies, bacterial pneumonia was a significant risk factor among 775 subjects who developed ischemic stroke (HR, 5.72; 95% CI, 4.92-6.65) and 193 subjects who developed hemorrhagic stroke (HR, 5.33; 95% CI, 3.91-7.26). Conclusion: The risks of developing ischemic stroke and hemorrhagic stroke are significant following bacterial pneumonia infection. The risk factors, clinical outcomes, and the disease course should also be profiled to better inform the monitoring of stroke development and the clinical management of bacterial pneumonia patients.
Keywords: infectious etiology